2013
DOI: 10.1159/000354840
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Revised International Prognostic Scoring System for Patients with Myelodysplastic Syndromes

Abstract: The objective of this study is to externally validate the recently published Revised International Prognostic Scoring System (IPSS-R) for myelodysplastic syndrome (MDS) and compare it with the International Prognostic Scoring System (IPSS). We conducted a retrospective study of 173 adult MDS patients who had not received disease-altering treatment. Using the Cox hazard method, we found the IPSS-R to be a significant predictor of survival (p < 0.001, hazard ratio, HR = 1.82, 95% confidence interval, CI 1.57-2.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
0
10
0
1
Order By: Relevance
“…The IPSS‐R and WPSS scoring systems are more accurate than the IPSS in estimating survival . In addition, the IPSS‐R has been validated in several independent datasets , whereas there have been few validations of the WPSS in large datasets. We confirmed the predictive value of the WPSS in a cohort of 598 patients ( P < 0.001 for trend), and our results further showed that the IPSS‐R, which was based on data from untreated patients, was a good predictor of survival in MDS patients who had received treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The IPSS‐R and WPSS scoring systems are more accurate than the IPSS in estimating survival . In addition, the IPSS‐R has been validated in several independent datasets , whereas there have been few validations of the WPSS in large datasets. We confirmed the predictive value of the WPSS in a cohort of 598 patients ( P < 0.001 for trend), and our results further showed that the IPSS‐R, which was based on data from untreated patients, was a good predictor of survival in MDS patients who had received treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with IPSS, the IPSS-R split patients with fewer than 5% BM blast into those with 0%-2% and greater than 2% to fewer than 5%, incorporated more sophisticated cytogenetic classification to separate patients into five, rather than three risk subtypes, and scored the depth of cytopenias to improve prognosis assessment for primary MDS patients [4]. It has been shown that IPSS-R predicts survival and leukemic evolution in MDS patients significantly better than IPSS in Western countries [5][6][7][8]. Since the demographics and disease natures in MDS patients are different between Asian and Western countries [9][10][11][12], it is unclear whether this new risk model is similarly useful for risk stratification of MDS in Asia.…”
Section: Introductionmentioning
confidence: 99%
“…Although the revised IPSS (IPSS‐R) showed improved prognostic precision over the IPSS, both the IPSS and the IPSS‐R were developed using cohorts of untreated patients (Greenberg et al , , ). The IPSS‐R has subsequently been shown to have prognostic value among treated MDS patients in retrospective analyses (Lamarque et al , ; Mishra et al , ; Savic et al , ; Voso et al , ; Neukirchen et al , ).…”
mentioning
confidence: 99%